A Dual‐Function Carbon Quantum Dot Fluorescent Probe for the Detection of Fe3+ and Sunset Yellow. Issue 40 (25th October 2022) - Bao, Wenbin; Lan, Yuwei; Lu, Haiqin; Li, Guowei; Yu, Meihua; Yang, Jiachu; Wei, Liubai; Su, Qionghua
Abstract: There are few researches on the application of multifunctional carbon quantum dots (CQDs) in analysis and detection. In this study, carbon quantum dots (CQDs) with dual‐function detection were synthesized by the one‐step hydrothermal method with citric acid as the carbon source and o‐phenylendiamine as the nitrogen source to detect Fe 3+ and sunset yellow. The morphology of the prepared CQDs and the surface functional groups were characterized using TEM, FTIR, XPS, UV‐Vis spectroscopy, and fluorescence spectrophotometer. The results show that the morphology of CQDs is nearly spherical and well dispersed, with a particle size range of 1.24∼6 nm and the average particle size was 3.23 nm. The surface of the CQDs has hydrophilic groups, such as OH, −COOH and −NH2 . CQDs exhibited good acid and alkali resistance, salt resistance, and photobleaching resistance under different conditions. The detection limits of CQDs for Fe 3+ and sunset yellow were 1.52 μM and 0.812 μM, respectively. The recoveries of actual samples were 96.65 %∼104.85 % and 95.4 %∼104.55 %, with relative standard deviations (RSDs) of less than 6 %. Therefore, CQDs can be employed as dual‐function fluorescent probes in the practical detection of samples and have promising application prospects. Abstract : Carbon Quantum Dots (CQDs) with dual‐function detection were synthesized by the one‐step hydrothermal method with citric acid as the carbon source and o‐phenylendiamine as the nitrogen source to detect Fe3+ and sunset yellow.The detection limits of CQDs for Fe3+ and sunset yellow were 1.52 μM and 0.812 μM, respectively. The recoveries of actual samples were 96.65 %∼104.85 % and 95.4 %∼104.55 %, with relative standard deviations (RSDs) of less than 6 %.